2013
DOI: 10.1136/thoraxjnl-2013-204457.34
|View full text |Cite
|
Sign up to set email alerts
|

S27 The effects of statin therapy on inflammatory markers in patients with copd: a double blind randomised controlled trial

Abstract: baseline and 7 weeks. Within and between group differences were analysed using paired and unpaired t-tests respectively. Results Please see table 1. Conclusion SPACE for COPD can improve dyspnoea and endurance capacity over 7 weeks to a similar level to PR, although it remains unclear to its noniferiority to PR. The SPACE for COPD programme does offer a number of health benefits despite it involving limited support and could offer a suitable alternative to patients with COPD who would otherwise not attend conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…A similar result was seen in a study conducted by Hothersall et al where the effect of daily oral atorvastatin treatment was found to reduce the number of macrophages in the sputum, although there was no improvement in the control of asthma symptoms [181]. In opposition to this, John et al found no significant difference in patients treated with simvastatin [182]. Finally, a recent study by Kauerova et al investigating the influence of statin treatment on macrophage polarization in human adipose tissue reported statin therapy to increase the proportion of M2-like macrophages compared to M1-like ones [103].…”
Section: Clinical Evidence For Inflammatory Effects Of Statins On Mac...supporting
confidence: 61%
“…A similar result was seen in a study conducted by Hothersall et al where the effect of daily oral atorvastatin treatment was found to reduce the number of macrophages in the sputum, although there was no improvement in the control of asthma symptoms [181]. In opposition to this, John et al found no significant difference in patients treated with simvastatin [182]. Finally, a recent study by Kauerova et al investigating the influence of statin treatment on macrophage polarization in human adipose tissue reported statin therapy to increase the proportion of M2-like macrophages compared to M1-like ones [103].…”
Section: Clinical Evidence For Inflammatory Effects Of Statins On Mac...supporting
confidence: 61%
“…Ultimately, 10 of the 20 studies were selected 4-5, 11, 14-20 ; of those not included, three were excluded because they did not use a placebo control [21][22][23] , three because they used the same dataset as another study included in this meta-analysis [24][25][26] , one because it was a post-hoc analysis of a large statin-heart failure RCT 27 , one because one-quarter of the recruited patients did not complete the study 28 , one because most of the patients did not fulfil GOLD criteria for COPD 29 , and one because no outcomes of interest were reported 30 . All the included trials were published as peer-reviewed articles, and all of them were in English.…”
Section: Study Descriptionmentioning
confidence: 99%
“…An investigation of the anti-inflammatory effects of statin therapy in COPD, while negative, provided novel thinking into treatments of the disease 42. For severe hospitalised exacerbations, the different response of eosinophilic and non-eosinophilic phenotypes further suggested that exacerbations may be a target for stratified treatment (and reducing harm of unnecessary drug prescription) 43.…”
Section: Copdmentioning
confidence: 99%